Hukum Jual Beli Online Dalam Perspektif Fikih Kontemporer - Robi’ah, Robi’ah; Syakinah, Syakinah; Hayati, Nurul Zahrah; Fatiha, Fatiha; Nisak, Rahmatun; Ningsih, Widia; Rizki, Muhammad (JURNAL MANAJEMEN PENDIDIKAN, 2026)
ONLINE SALES LAW IN THE PERSPECTIVE OF CONTEMPORARY FIQHThe rapid development of digital technology has significantly transformed economic transaction mechanisms, particularly through online buying and selling activities. This study aims to analyze the legal status of online transactions from the perspective of contemporary Islamic jurisprudence by examining the principles of muamalah, the validity of digital contracts, the clarity of transaction objects, the legal responsibilities of involved parties, and the relevance of these practices to the objectives of Islamic law (maqasid al-sharia). This research employs a library-based qualitative method by reviewing classical and contemporary fiqh literature, DSN-MUI fatwas, and regulations concerning digital transactions. The findings indicate that online buying and selling are permissible and valid in Islamic law as long as they fulfill elements of mutual consent, honesty, transparency, and clarity of the transaction object. Digital agreements conducted through approval clicks or electronic messages are recognized as valid forms of al-bay‘ bi al-mu‘āṭah. Furthermore, features such as refunds, returns, and marketplace security systems align with the concept of khiyar in Islamic jurisprudence. From the maqasid al-sharia perspective, digital transactions are allowed as long as they bring benefits and remain free from gharar, tadlis, exploitation, or data misuse. This study concludes that Islamic jurisprudence is dynamic and capable of adapting to contemporary developments, including the challenges of modern digital commerce.